Insulin Resistance Prevents AMPK-induced Tau Dephosphorylation through Akt-mediated Increase in AMPK(Ser-485) Phosphorylation - Kim, Bhumsoo (J Biol Chem, 2015)
Metabolic syndrome (MetS) is a cluster of cardiovascular risk factors including obesity, diabetes, and dyslipidemia, and insulin resistance (IR) is the central feature of MetS. Recent studies suggest that MetS is a risk factor for Alzheimer disease (AD). AMP-activated kinase (AMPK) is an evolutionarily conserved fuel-sensing enzyme and a key player in regulating energy metabolism. In this report, we examined the role of IR on the regulation of AMPK phosphorylation and AMPK-mediated Tau phosphorylation. We found that AMPK(Ser-485), but not AMPK(Thr-172), phosphorylation is increased in the cortex of db/db and high fat diet-fed obese mice, two mouse models of IR. In vitro, treatment of human cortical stem cell line (HK-5320) and primary mouse embryonic cortical neurons with the AMPK activator, 5-aminoimidazole-4-carboxamide 1-β-d-ribofuranoside (AICAR), induced AMPK phosphorylation at both Thr-172 and Ser-485. AMPK activation also triggered Tau dephosphorylation. When IR was mimicked in vitro by chronically treating the cells with insulin, AICAR specifically induced AMPK(Ser-485), but not AMPK(Thr-172), hyperphosphorylation whereas AICAR-induced Tau dephosphorylation was inhibited. IR also resulted in the overactivation of Akt by AICAR treatment; however, preventing Akt overactivation during IR prevented AMPK(Ser-485) hyperphosphorylation and restored AMPK-mediated Tau dephosphorylation. Transfection of AMPK(S485A) mutant caused similar results. Therefore, our results suggest the following mechanism for the adverse effect of IR on AD pathology: IR → chronic overactivation of Akt → AMPK(Ser-485) hyperphosphorylation → inhibition of AMPK-mediated Tau dephosphorylation. Together, our results show for the first time a possible contribution of IR-induced AMPK(Ser-485) phosphorylation to the increased risk of AD in obesity and diabetes.